2012
DOI: 10.3892/or.2012.1692
|View full text |Cite
|
Sign up to set email alerts
|

Metadherin regulates radioresistance in cervical cancer cells

Abstract: Abstract. Metadherin (MTDH) promotes cancer metastasis, chemoresistance, invasion and angiogenesis. Upregulation of MTDH is correlated with both progression and poor clinical outcome of many types of cancers; however, there is currently no information regarding the role of MTDH in radiation sensitivity. Here, we investigated the effects of MTDH on the radiosensitivity of cervical cancer cells using the SiHa cell line. We discovered that cervical cancer cells in which MTDH was knocked down had significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Recently, Zhao et al (2012) showed a possible involvement of AEG-1 in radiation response in the cervical cancer cell line SiHa. The AEG-1 knock-down resulted in a decreased survival and G2 phase arrest after radiation as well as in radiation-induced apoptosis in those cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhao et al (2012) showed a possible involvement of AEG-1 in radiation response in the cervical cancer cell line SiHa. The AEG-1 knock-down resulted in a decreased survival and G2 phase arrest after radiation as well as in radiation-induced apoptosis in those cells.…”
Section: Discussionmentioning
confidence: 99%
“…Once expressed, AEG-1 can activate several oncogenic signalling pathways such as PI3K/Akt, MAPK, Wnt, RNA interference, and NF- κ B that are involved in proliferation, chemoresistance, invasion, angiogenesis, and metastasis (Sarkar et al , 2008; Lee et al , 2008; Emdad et al , 2009; Yoo et al , 2011). Recently, Zhao et al (2012) showed that AEG-1 affects the survival, DNA repair, and cell cycle distribution after radiation in a cervical cancer cell line.…”
mentioning
confidence: 99%
“…Recent results have also indicated that AEG-1/MTDH affects the radiosensitivity of cervical cancer cells (51). In summary, it has become apparent that AEG-1/MTDH is an important oncogene, which is overexpressed in numerous human cancer types.…”
Section: Oncogenic Functions Of Aeg-1/mtdhmentioning
confidence: 99%
“…Current and future studies must focus on the translational aspects of AEG-1/MTDH, and on the understanding of AEG-1/MTDH function in physiological and pathological processes using transgenic and knockout mouse models in cancer. The knockdown of AEG-1/MTDH (32,33,41,45,51,93,94) or AEG-1/MTDH inhibition (92,95,96) can inhibit transformation, proliferation, the evasion of apoptosis, migration and invasion, metastasis, angiogenesis and chemoresistance. In summary, the functional characterization of AEG-1/MTDH as a novel protein with poorly-characterized functions is urgently required to realize its full therapeutic potential.…”
Section: Clinical Translation and Therapeutic Targeting Strategymentioning
confidence: 99%
“…Our previously studies show that it is widely over-expressed in many breast cancer cell lines or tumors and plays a crucial role in tumor invasion, metastasis and drug resistance [7,8,9,10]. Nearly 50% ER-positive breast cancer patient express high concentration of MTDH by immunohistochemicial method and was significantly correlated with an aggressive phenotype and a poor prognosis [11].…”
Section: Introductionmentioning
confidence: 99%